Analisis Pengukuran Kinerja Rumah Sakit Dengan Metode Balanced Scorecard(Studi Kasus pada Rsud Pandan Arang Boyolali Dan Rsud Kota Semarang) - Hardhiyani, Farisa; , Andy Dwi Bayu Bawono, S.E., M.Si., Ph.D (2017)
The purpose of this study is to compare an evaluation ofBalanced Scorecard methodimplementation in measuring the performance between RSUD Pandan Arang Boyolali and RSUD Semarang. This Balanced Scorecard is a tool that viewed the hospital performancebased on four perspectives namely financial, customer, internal business processes, and learning and growth perspective. ThisBalanced Scorecardmethod would help both of hospital to develop their performance evaluation system for improving their services. This study uses RSUD Pandan Arang Boyolali and RSUD Semarang for the case study by using primary and secondary data from 2013 to 2015. This study intend to obtain data relating to the agency's performance measurement with the Balanced Scorecard concept. The result showsthat the overall performance of RSUD Pandan Arang Boyolali and RSUD Semarang considered sufficient in terms of both financial and non-financial perspectives. However, based on the Balanced Scorecard result, RSUD Pandan Arang has a better performance measurement result compararingto RSUD Semarang in term of financially and non financially aspects. Keywords: balanced scorecards, performance measurement,hospital